The Heat Is on Public Health - Binns, Colin; Low, W. (Sage Publications, Inc., 2013)
The Asia-Pacific Journal of Public Health has been at the forefront of raising public health issues emerging in our region. In 2011, the journal published a supplement devoted to the issue of climate change and public health. Events that were predicted to occur at some time in the future appear to be coming sooner than expected. The world has just experienced its hottest decade ever, and Australia has just sweltered under its hottest summer. During this period in Australia, the short term health effects were evident with an increase in heat-related illnesses. These prolonged periods of higher temperatures have an effect on human health, animals, ecosystems, and agriculture, including food production. Heat kills more Australians than any other extreme weather event.